Hybrid engineering incorporating salt marsh terraces into sea wall repair maintains their defence function and creates new habitats - Slee, Nicola J.D.; Gardiner, Tim; Underwood, Graham J.C. (Estuarine, coastal and shelf science, 2023)
Sea walls are widely-used engineered structures designed to protect low lying land from flooding. Rising sea levels and coastal erosion threatens sea wall integrity and requires maintenance and repair. As an alternative to conventional repairs, a hybrid engineering design incorporating sediment-filled terraces to allow the development of salt marsh has been trialled to protect sea walls in the Colne-Blackwater Estuary complex, Essex. U.K. Over a 10 year period, three different trajectories of development were measured. Salt marsh halophytes colonised 7 out of 15 terraces, with % plant cover ranging between 5% and 170%. Halophyte species richness on terraces ranged from 1 to 8 species (average = 1.7 per 4 m2), compared to existing salt marsh adjacent to the repairs (max. species richness 9, average 6.85), with positive significant relationships between % halophyte cover and halophyte richness and between % halophyte cover and sediment water content (19–51% on terraces). Organic carbon content was significantly lower on the terraces compared to existing salt marsh (7–19 % AFDW on terraces, 17–24% in marsh sediments). A sediment shear strength of 30 kPa was optimal for % plant cover on terraces. The height of the terraces relative to tidal inundation was a key determinant of successful halophyte colonisation. A second trajectory (3 of 15 terraces) resulted in development of macro- and microalgal mats, up to 100 % cover. Both these trajectories resulted in up to 25 cm of vertical sediment accretion. Shell banks formed on 2 terraces. Seven terraces were subject to erosion, associated with desiccation and absence, or loss, of halophyte cover. Eroding terraces showed both surface lowering (20–30 cm) and massive sediment failure (blocks >50 cm deep falling away). After a decade, protection of the sea wall was still provided by 14 of the 15 terraces, with only one having to be rebuilt. Utilising a nature-based approach incorporating sea wall terraces resulted in the formation of three types of linear habitat (salt marsh, microbial mats, shell banks) providing some ecosystem services that would not have existed if a conventional hard-engineered repair had been used. [Display omitted] •Building clay-filled terraces into sea wall repair successfully created new habitats while maintaining sea defence capability.•Over 10 years, 7 terraces developed salt marsh, 3 developed microbial mat assemblages, 2 shell banks and 3 terraces remained bare clay.•Tidal height position was a key factor in determining success for salt marsh development.•Halophyte species richness and percent cover were correlated, some terraces matched adjacent salt marsh.•Both salt marsh and microbial mat assemblages supported sediment accretion. Only one terrace had to be repaired after nine years.